Broad spectrum of autoantibodies in Wiskott-Aldrich Syndrome (WAS) and X-linked Thrombocytopenia (XLT) - Crestani, Elena (J Allergy Clin Immunol, 2015)
Using a protein microarray, a broad spectrum of autoantibodies were demonstrated in patients with either Wiskott-Aldrich syndrome (WAS) or with X-linked thrombocytopenia (XLT), indicating that immune dysregulation is an integral component of both diseases.